Educação ambiental na avaliação de impacto ambiental: análise dos programas de educação ambiental no âmbito do licenciamento ambiental federal de hidrelétricas - Carvalho, Denici Laura (2019)
There are several concepts and political-pedagogical tendencies of Environmental Education developed through environmental movements, but mainly due to the great scientific contribution of researchers and professionals from governmental institutions. Many of these trends are included in the Environmental Education Programs (PEAs) of environmental licensing processes. PEAs, which usually make up the Basic Environmental Plans (PBAs), are among the actions to compensate and mitigate the impacts of the projects in licensing processes and must follow the various guidelines and procedures that regulate and guide their development, implementation, monitoring and evaluation. They are important mainly for projects with large socio-environmental impacts. The present research aims at evaluating the effectiveness of the Environmental Education Programs proposed in the scope of the federal environmental licensing of hydroelectric power plants against the legislation and best practices of the Environmental Impact Assessment and to analyze the type of political-pedagogical tendency of the proposed environmental education. In order to meet the first objective, a set of indicators was elaborated according to good practices and legal regulations, with the indicators being evaluated in the attended, attended and not partially; for the second, a reference framework with different dimensions of three macro trends of environmental education was used: conservationist, pragmatic and critical. Fifteen hydroelectric power licensing processes conduced by the Brazilian Institute for the Environment and Renewable Natural Resources (IBAMA) were analyzed, and the information was compiled from the Environmental Impact Statement (EIS) and the Basic Environmental Plan (PBA). Through analyzes, it was observed that the environmental education programs partially comply with legal guidelines and good practices. From the comparisons between the two types of studies, the EIS, for the most part, obtained results with partial compliance or did not meet the indicators; for the PBA, the environmental education programs had more diversity in the results, and better evaluations of attendance to the indicators could be noted. Even so, compliance with the indicators was not satisfactory, especially for those who reflect the practice required by the legislation. As for the analysis of political-pedagogical tendencies, the conservationist macro-tendency was predominant in the two environmental studies, followed by pragmatic and critical. In this way, the need for more effective environmental programs focused on a critical education, not only compliant with regulations, but with an environmental education rich in opportunities for social interaction among the different stakeholders.